The Effect of Orthorexia Nervosa Levels of Nursing Students and Diet Behaviors and Socio-Demographic Characteristics. Issue 4 (4th July 2019) - Aktürk, Ümmühan; Gül, Ebru; Erci, Behice
ABSTRACT: This study was conducted to determine the Orthorexia Nervosa (ON) level in the nursing faculty students and the effective factors. This was a correlational, descriptive study. This study recruited N = 558 student nurses from one university. Questionnaire and the ON Scale were used to collect the data of the study. The descriptive characteristics of the nursing students were stated by the number, percentage, mean, standard deviation, linear and logistic regression analysis were used. This study, only the cut-off point of the Scale (≤33) was used. It was determined that having limited diet, weight satisfaction, gender, and health problems had an effect size of 0.14 on the tendency of the nursing students for the ON behaviors. The study highlights that middle levels of ON identified in the literature are seen in student nurses, and the factors affecting it were investigated.